Ophthalmological complications associated with clinically significant carotid stenosis - Rozegnał-Madej, Agnieszka; Bielecka, Emilia; Święch-Zubilewicz, Anna; Żarnowski, Tomasz; Karakuła, Wacław; Zubilewicz, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
The aim of the study was to show ocular manifestations in carotid artery occlusive disease, with pathogenesis, diagnostic and therapeutic abilities of this changes. Carotid arteries are the main route by which the blood is supplied to the cerebrum and eyes. Clinical significant carotid artery stenosis is mainly caused by atherosclerosis. Most frequent neurological symptoms are transient ischemic attacks (TIA) and temporary visual loss (amaurosos fugax) are most common ocular symptoms. Other ocular pathologies in fundus examination are retinal embolies, retinal vein occlusion, anterior ischemic optic neuropathy, ocular ischemic syndrome or glaucoma. Most dangerous complications are stroke, blindness, or even patients death. Besides clinical examination the diagnosis is usually confirmed by carotid artery color Doppler ultrasound, magnetic resonance angiography and retinal fluorescein angiography. It is important to refer a patient with suspected or confirmed significant carotid artery stenosis for appropriate evaluation and treatment to a endovascular surgeon.